Embates representacionais em busca de uma personagem: Maria Lacerda de Moura no tráfico de luzes e sons - (:unkn) unknown (Ministério Público do Estado da Bahia, 2009)
From the documentary Maria Lacerda de Moura: trajetória de uma rebelde, the present article analyzes the delicate exercise of re-creating the biography of historical personalities in a film, where the conjunction of different points of view, film making languages and interpretations,as well as the collision between image and text, evocative language and historical account,disclose significantly the open, imaginative, representational status, subject to different appropriations, of social and individual realities which are the objects of the social sciences.
Representational collisions in quest of a character: Maria Lacerda de Moura in the traffic of lights and sounds
Keywords: Linguagem audiovisual; Ciências Sociais; Representação fílmica; Reconstituição histórico-biográfica; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO